Analysis of polymorphisms in Interleukin 10, NOS2A, and ESR2 genes in chronic and aggressive periodontitis - Virginia Régia Souza SILVEIRA; Suzane Cristina PIGOSSI; Raquel Mantuaneli SCAREL-CAMINAGA; Joni Augusto CIRELLI; Rodrigo RÊGO; Nádia Accioly Pinto NOGUEIRA
Abstract The objective of this study was to investigate the association between single nucleotide polymorphisms (SNPs) in the IL10, NOS2A, and ESR2 genes and chronic periodontitis (CP) and aggressive periodontitis (AgP). Three groups of patients underwent periodontal and radiographic evaluations: CP (n = 61), AgP (n = 50), and periodontally healthy (control group=61). Genomic DNA was extracted from oral epithelial cells and used for genotyping by real-time polymerase chain reaction using TaqMan® probes. The investigated SNPs were: -1087G > A, -819C > T and -592C > A in the IL10; +2087G > A in the NOS2A, and +1730G > A in the ESR2 gene. Differences in genotype and allele frequencies of each polymorphism and some individual characteristics were analyzed using the chi-square test and multivariate logistic regression analysis. Analysis of SNPs and haplotypes in the IL10 and SNP in the ESR2 gene did not present any significant association with AgP or CP. The +2087G allele of the NOS2A gene tended to be significantly associated with periodontal disease. Patients carrying the genotype +2087GG in the NOS2A gene were genetically protected against the development of CP (p = 0.05; OR = 0.44; 95%CI = 0.20-0.95). This result showed greater significance when patients with AgP and CP were combined (total PD) (p = 0.03; OR = 0.46; 95%CI = 0.23-0.92). In conclusion, the studied Brazilian population had a significantly higher frequency of the GG genotype for the +2087 SNP in the NOS2A gene in individuals without periodontitis, although statistical significance was not maintained after multiple logistic regression.